A composite measure of habitat loss for entire assemblages of species. Issue 6 (24th June 2019) - Simmonds, Jeremy S.; Watson, James E. M.; Salazar, Alvaro; Maron, Martine
Abstract: Habitat destruction is among the greatest threats facing biodiversity, and it affects common and threatened species alike. However, metrics for communicating its impacts typically overlook the nonthreatened component of assemblages. This risks the loss of habitat going unreported for species that comprise the majority of assemblages. We adapted a widely used measure for summarizing researcher output (the h index) to provide a metric that describes natural habitat loss for entire assemblages, inclusive of threatened and nonthreatened species. For each of 447 Australian native terrestrial bird species, we combined information on their association with broad vegetation groups with distributional range maps to identify the difference between the estimated pre‐European and current extents of potential habitat, defined as vegetation groups most closely associated with each species. From this, we calculated the loss index (LI), which revealed that 30% of native birds have each lost at least 30% of their potential natural habitat (LI = 30). At the subcontinental scale, LIs ranged from 15 in arid Australia to 61 in the highly transformed southeastern part of the country. Different subcomponents of the assemblage had different LI values. For example, Australia's parrots ( n = 52 species) had an LI of 38, whereas raptors ( n = 32 species) had an LI of 25. The LI is simple to calculate and can be determined using readily available spatial information on species distributions, native vegetation associations, and human impacts on natural land cover. This metric, including the curves used to deduce it, could complement other biodiversity indices if it is used for regional and global biodiversity assessments that compare the status of natural habitat extent for assemblages within and among nations, monitor changes through time, and forecast future changes to guide strategic land‐use planning. The LI is an intuitive tool that can be used to summarize and communicate how human actions affect whole assemblages, not just threatened species. Abstract : Article impact statement : The habitat loss index allows for effect of habitat removal on multispecies assemblages to be easily described and systematically tracked. Abstract : Una Medida Compuesta de la Pérdida del Hábitat para Ensamblajes Enteros de Especies Resumen: La destrucción del hábitat está entre las principales amenazas para la biodiversidad, además de que afecta tanto a especies comunes como a las especies amenazadas. Sin embargo, las medidas para comunicar los impactos de esta destrucción generalmente ignoran al componente no amenazado de los ensamblajes de especies. Esto genera el riesgo de que la pérdida del hábitat pase desapercibida en el caso de las especies que conforman a la mayoría de los ensamblajes. Adaptamos una medida de uso amplio para resumir las contribuciones de los investigadores (el índice h) y así proporcionar una medida que describa la pérdida del hábitat para ensamblajes enteros, incluyendo a las especies amenazadas y a las no amenazadas. Para cada una de las 447 especies de aves terrestres nativas a Australia, combinamos la información sobre su asociación con grupos generales de vegetación con mapas de extensión de su distribución para identificar la diferencia entre la extensión estimada previa a la llegada de los europeos y la extensión actual de los hábitats potenciales, definidos como los grupos de vegetación asociados más cercanamente con cada especie. A partir de esto, calculamos el índice de pérdida (LI, en inglés), el cual reveló que el 30% de cada una de las aves nativas ha perdido al menos el 30% de su hábitat natural potencial (LI = 30). A escala subcontinental, los LI variaron desde 15 para las partes áridas de Australia, hasta 61 en la altamente transformada parte sureste del país. Los diferentes subcomponentes del ensamblaje tuvieron diferentes valores de LI. Por ejemplo, los loros australianos ( n = 52 especies) tuvieron un LI de 38, mientras que las aves rapaces ( n = 32 especies) tuvieron un LI de 25. El LI es fácil de calcular y puede determinarse usando información espacial que ya se encuentra disponible, las asociaciones con la vegetación nativa y los impactos humanos sobre la cobertura natural del suelo. Esta medida, incluyendo las curvas que se usan para deducirla, podrían complementar otros índices de biodiversidad si se usa para evaluaciones de la biodiversidad regional y global, las cuales comparan el estado de la extensión del hábitat natural para ensamblajes dentro y entre las naciones, monitorean cambios a través del tiempo y pronostican cambios futuros que guíen la planeación del uso de suelo estratégico. El LI es una herramienta intuitiva que puede usarse para resumir y comunicar cómo las acciones humanas afectan a ensamblajes enteros, no sólo a las especies amenazadas. 摘要: 生境破坏是生物多样性面临的最大威胁之一, 它同时影响着常见种和濒危种。然而, 对生境破坏影响的指标却常常忽略群落聚合体中的非濒危组分, 这有可能导致群落中大部分物种的生境丧失得不到报告。我们在常用的总结研究者产出 (h 指数) 方法的基础上, 创建了一个描述整个群落聚合体 (包括濒危和非濒危物种) 自然生境丧失的指标。利用这个方法, 我们将澳洲 447 种本土陆生鸟类所在的植被群信息与分布图相结合, 确定了它们在前欧洲时期和当前估计的潜在生境范围之间的差异, 其中对潜在生境的定义是那些与每个物种相关度最高的植被群。我们用这个模型计算了丧失指数, 结果显示有 30%的本土鸟类分别丧失了至少 30%的潜在自然生境 (丧失指数为 30) 。在次大陆尺度上, 丧失指数介于 15 (澳洲干旱地区) 到 61 (东南部高度改造生境) 之间。含有不同组分的群落聚合体有不同的丧失指数, 例如, 澳洲鹦鹉 (52 个物种) 的丧失指数为 38, 而猛禽 (32 个物种) 的丧失指数为 25。丧失指数计算简单, 可以利用现成的物种空间分布、原生植被群以及人类对自然土地覆盖的影响等信息。在比较国家内部或国家之间群落聚合体的自然生境情况、监测其随时间的变化, 及预测未来变化以指导土地利用战略规划时, 可以用丧失指数和用于估计指数的曲线作为其它生物多样性指标的补充, 以评估区域和全球生物多样性。丧失指数是一项直观的工具, 它可以用于总结和探讨人类行为对整个群落聚合体的影响, 而不仅限于濒危物种。 【翻译: 胡怡思; 审校: 聂永刚】